PEMANFAATAN WORDWALL SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA SD/MI - Argameiswari, Azalia; Anugrah Dwi Afnafika; Alaika Rahmah; Roni Muslikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery is a fundamental competence that elementary school students need to acquire as a foundation for developing their English language skills. However, the continued use of conventional teaching methods often limits students' active participation and reduces their motivation to learn new vocabulary. One alternative to address this issue is the integration of digital learning media, such as Wordwall, which can promote a more interactive and engaging learning environment. This study aims to analyze the use of Wordwall as an interactive learning medium to improve English vocabulary mastery among elementary school students. The study employed a library research method using a qualitative descriptive approach. Data were collected through the identification, selection, and review of ten relevant scientific articles, which were subsequently analyzed using the content analysis technique to produce a comprehensive synthesis of previous research findings. The findings indicate that Wordwall functions as an effective interactive learning medium by enhancing students' learning motivation, participation, engagement, and self-confidence during English learning activities. Furthermore, the implementation of Wordwall through various game-based learning activities effectively supports students in recognizing, understanding, memorizing, and applying English vocabulary more efficiently. The findings also reveal that the use of Wordwall contributes positively to the development of active, innovative, collaborative, and student-centered English learning at the elementary school level. Overall, this study confirms that Wordwall can be utilized as an alternative digital learning medium to support the improvement of English vocabulary mastery among elementary school students.